Evaluation of a Large Scale Advance Care Planning Co-Design Education Program for Chinese-Speaking People in Australia. (February 2022) - Wong, Aaron Kee Yee; Collins, Anna; Ng, Andrew; Buizen, Luke; Philip, Jennifer; Le, Brian
Background: Advance care planning (ACP) is important, however ethnic minorities have half the completion rates in the United States compared to Caucasian counterparts, and in Australia only 3.5% of advance directives were completed by those overseas-born.Educational intervention improves ACP knowledge and subsequent uptake. We evaluated immediate and longer-term outcomes of a co-designed ACP education toolkit in Chinese-speaking people in Victoria, Australia. Methods: We conducted a cross-sectional survey of Chinese-speaking community members who participated in a co-designed Chinese ACP educational workshop. A self-selected subgroup were subsequently contacted 6 months later to determine longer-term outcomes. Results: Of 519 attendees across 17 workshops, 325 (63%) completed the evaluation. The majority (63%;n = 206) were previously unaware of ACP. Perception of receipt of useful information positively correlated with motivation to undertake ACP ( r = 0.3486, p < 0.001). Of the 70 participants who consented to follow up, 36% (n = 26) agreed to participate in structured telephone interviews. English speakers were more likely to have undertaken ACP (n = 6 vs n = 3). ACP completion was not associated with being a carer or suffering from cancer or chronic illness. Conclusions: This first Australian study evaluating ACP co-design education implementation outcomes in Chinese-speaking people supports that motivation to undertake ACP is related to knowledge, albeit a modest ACP uptake in a small follow up sample. Clinicians should note that this assists with ACP uptake, with likely downstream improved health outcomes. This co-designed toolkit could be helpful in increasing ACP uptake. Future engagement by Chinese language societies to overcome further barriers to ACP is needed.